The role of connexin 37 gene polymorphism (1019C > T; Pro319Ser) in cardiovascular disease - Pitha, J.; Pithova, P.; Hubacek, J.A. (Вiopolymers and Cell, 2011)
In spite of the strong prognostic value of all traditional cardiovascularrisk factors, still striking differences exist in the prevalence of clinical events between patients at apparently similar risk. One of the main reasons is different genetic background. One of recently discussed candidate genes for cardiovascular disease is the gene for the protein Connexin 37 (Cx37). This protein is a part of gap junctions responsible for communications between cells including cells in the vessel wall. Studies focused on the association between Cx37 gene polymorphism (1019C > T; Pro319Ser) and cardiovascular disease demonstrate inconsistent results. Our findings in 1.316 men and women indicated that the Cx37 gene polymorphism (genotype CC) is significantly associated with acute coronary syndrome in non-smoking women. In addition, in urban and rural women from general population (n = 1.056) with impaired fasting glycaemia the same genotype is associated with increased intima media thickness of carotid arteries measured by ultrasound. Finally, in 289 women with diabetestype 1 or 2, and in 208 women from general population with central obesity, the CC genotype was associated with lower ankle brachial blood pressure index. These data indicate that Cx37 gene polymorphism could have gender- and smoking-dependent effects on acute coronary events and glucose dependent effect on atherosclerosis in women. Keywords: connexin 37 gene polymorphism, atherosclerosis, acute coronary syndromes, women smoking, glycaemia.